Methylphenidate can help reduce weight, appetite, and food intake—a narrative review of adults’ anthropometric changes and feeding behaviors - Vedrenne-Gutiérrez, Fernand; Yu, Sion; Olivé-Madrigal, Anna; Fuchs-Tarlovsky, Vanessa (Frontiers in Nutrition, 2024)
Treating obesity is a global challenge due to its complexity and associated comorbidities, including cardiovascular disease, diabetes, and cancer. Current treatments, such as lifestyle changes and bariatric surgery, often pose risks or are challenging to follow. Pharmacological interventions offer promising alternatives, especially those that act on the brain's reward system. Methylphenidate (MPH) has been successfully used to treat Attention Deficit and Hyperactivity Disorder in adults and children. MPH can modulate dopamine levels in different brain areas to regulate appetite and feeding behaviors. This narrative review evaluates how MPH can regulate food intake, feeding behaviors, body weight, and other anthropometric indicators in adults with obesity or overweight. We selected 39 studies using a PICO approach. Our analysis includes 14 randomized controlled trials as well as 3 observational studies. Findings suggest that MPH can lead to a modest 1 -2% weight loss, and appetite suppression. The effect appeared stronger in women, who experienced greater reductions in appetite and food cravings, while studies may remain underpowered to detect effects in men. This review highlights the possible role that MPH could play in treating obesity. However, it underscores the need to evaluate MPH's safety profile, and long-term efficacy still needs to be assessed in adults with obesity and overweight.